2013
DOI: 10.1111/liv.12195
|View full text |Cite
|
Sign up to set email alerts
|

HGF and SDF‐1‐mediated mobilization of CD133+BMSC for hepatic regeneration following extensive liver resection

Abstract: HGF and SDF-1 are required for effective HSC mobilization and homing to the liver after hepatic resection. These findings have significant implications for potential therapeutic strategies targeting chemotactant modulation and stem cell mobilization for liver protection and regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
0
25
1
Order By: Relevance
“…More recently, an increasing appreciation for the importance of splenectomy in cell transplantation has been focused on molecules that affect cell homing . SDF‐1 and its receptor, CXCR4, are involved in cell recruitment . Our results showed that cell migration was notably weakened by neutralizing CXCR4, suggesting the SDF‐1/CXCR4 signalling might play an important role in the recruitment of ADSCs into liver.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…More recently, an increasing appreciation for the importance of splenectomy in cell transplantation has been focused on molecules that affect cell homing . SDF‐1 and its receptor, CXCR4, are involved in cell recruitment . Our results showed that cell migration was notably weakened by neutralizing CXCR4, suggesting the SDF‐1/CXCR4 signalling might play an important role in the recruitment of ADSCs into liver.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, increasing numbers of studies have demonstrated that mesenchymal stem cell infusion is a promising application for cirrhosis treatment because of the infused stem cells' ability to migrate into the injured site to regenerate tissues; this homing ability was associated with an increase in the circulating levels of cytokines . Stromal cell‐derived factor‐1 (SDF‐1) is thought to play a critical role in the homing effect of stem cells .…”
mentioning
confidence: 99%
“…Owing to their mitogenicity, HGFs play an important role in liver development, maturation, and regeneration (Suárez-Causado et al, 2015). HGFs can stimulate the proliferation of hepatocytes, various epithelial cells, endothelial cells, chondrocytes, and neurocytes, promote various types of cellular movement and morphological changes (Lehwald et al, 2014), and inhibit apoptosis (Gohda, 2002). To this effect, HGF addition is commonly used for liver stem cell differentiation in in vitro experiments (Liu et al, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SDF-1a plays an important and unique role in the regulation of stem cell trafficking, and governs the migration of MSCs, their homing in major bone marrow, and accumulation of immune cells in inflammatory tissue Haider et al 2008;Kucia et al 2004). Evidences from in vitro and in vivo studies have shown that SDF-1a is a potent chemoattractant for MSCs (Zhou et al 2007;Lehwald et al 2014). Recently, many studies have proved that MSCs migration was regulated by SDF1a (Lu et al 2012;Zhou et al 2007).…”
Section: Introductionmentioning
confidence: 94%